2018
DOI: 10.1186/s12870-018-1421-3
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific chloroplast genome sequence diversity and genomic resources in Diospyros

Abstract: BackgroundFruits of persimmon plants are traditional healthy food in China, Korea and Japan. However, due to the shortage of morphological and DNA markers, the development of persimmon industry has been heavily inhibited.ResultsChloroplast genomes of Diospyros cathayensis, D. virginiana, D. rhombifolia and D. deyangensis were newly sequenced. Comparative analyses of ten chloroplast genomes including six previously published chloroplast genomes of Diospyros provided new insights into the genome sequence diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
56
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 51 publications
(37 reference statements)
13
56
1
1
Order By: Relevance
“…The chloroplast genome is conserved similar to the majority of plants; no rearrangement events were detected in all species. The mVISTA results and nucleotide diversity tests indicate high similarities between the chloroplast genomes implying that the divergence of the Atractylodes chloroplast genome is lower than that of other species [6,37,38].…”
Section: The Chloroplast Genome Of Atractylodesmentioning
confidence: 92%
See 1 more Smart Citation
“…The chloroplast genome is conserved similar to the majority of plants; no rearrangement events were detected in all species. The mVISTA results and nucleotide diversity tests indicate high similarities between the chloroplast genomes implying that the divergence of the Atractylodes chloroplast genome is lower than that of other species [6,37,38].…”
Section: The Chloroplast Genome Of Atractylodesmentioning
confidence: 92%
“…The evolution rate is relatively moderate and is between the nuclear and mitochondrial genome [2]. Due to the lack of recombination, small genome size and high copy number per cell [3,4], complete chloroplast genome sequences have been extensively used in phylogenetics analysis and species identi cation [5,6]. The results showed that the chloroplast genome contains additional information to improve phylogenetic analysis [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Complete plastomes have been suggested as having the potential to increase species resolution among plant species [18,19], and have been used to discriminate species in a number of taxa that are difficult to resolve (e.g., Ficus [20]; Panax [22]; Taxus [24]; Diospyros [25]). In our study, seven of the nine species (78%, Table 2) in Calligonum that have more than one accession, were correctly identified to species.…”
Section: Taxonomic Resolution Based On the Complete Plastomementioning
confidence: 99%
“…A genetic sequence of the complete plastome can be easily obtained through a genome skimming approach of highcopy genomic targets, where its conserved gene content, organization and, structure makes it easy to assemble and annotate [17]. Notably, the compete plastome, in addition to all the standard plastid barcodes, should provide a wealth of informative and variable sites for the genetic identification and phylogenetic analyses of plant species [18,19]: also see e.g., Ficus [20], Lilium [21], Panax [22], Stipa [23], Taxus [24], and Diospyros [25].…”
Section: Introductionmentioning
confidence: 99%
“…The plants are often used as ornamental plants and folk herbal medicine. In the present study, we assembled the complete chloroplast genome sequence of G. trifoliata based on the next-generation sequencing method (Dong et al 2017;Li et al 2018). Our aims were to establish and characterize the organization of the complete chloroplast genome of G. trifoliata and to calibrate the phylogenetic position of G. trifoliata based on phylogenomic analysis.…”
mentioning
confidence: 99%